Model Evaluasi Kinerja Lembaga Keuangan Mikro Syariah Berbasis Konsep Mobadala, Kesetaraan Gender dan Inklusi Sosial. - Hazmi, Faiqul; Utami, Cahyaning Budi; Munasir; Chouarfa, Houda (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
This research aims to evaluate the performance of Islamic Microfinance Institutions (IMFIs) based on gender justice and social inclusion. This research focuses on IMFIs in 3 cities: Jepara, Kudus and Demak. Data collection techniques were carried out through observation, interviews, primary data documentation and secondary data collection in the form of financial reports. This research uses a decision support system tool, the Simple Additive Weighting (SAW) method, to measure the financial performance of Islamic banks from a gender perspective. The research results show (1) Apart from quantitative performance measurements, IMFIs need to consider qualitative measurement aspects, such as gender justice and social inclusion; (2) Preparation of a strategy model for evaluating IMFIs performance based on gender justice & social inclusion; (3) The proposed ranking model is an adaptation model for the Maqosid Syariah Index ranking by adding gender justice conception items to the construct in performance evaluation as part of the principles of Iqomatul Adli and elements of Al-Maslahah. Mobadalah-based gender justice is a theoretical concept that pursues fairness and reciprocity in granting rights and fair treatment of all individuals, regardless of sex or gender identity.